The domestic dimension of cross-border governance: Patterns of coordination and cooperation; Die innerstaatliche Dimension grenzüberschreitender Governance: Koordinations- und Kooperationsmuster - Tobias Chilla (Raumforschung und Raumordnung / Spatial Research and Planning, 2023)
Contemporary debates in border studies tend to see the national level as a rather residual category. There are, however, strong arguments that the national level still plays an important role for the governance of border regions. The question is what kind of formats are in place related to coordination and networking of border regions within national settings. The aim of this paper is to provide an exploratory typology of domestic governance settings. The underlying empirical study shows a large diversity of governance patterns in thirteen European countries. A synthetic typology reveals five approaches, namely centralist, decentral and selective coordination as well as transnational and laisser-faire approaches. On this basis, the explanatory factors of the revealed governance patterns are discussed. The state structure (federal, centralist) plays an important role. Moreover, contingent political strategies, embedded in political culture and path dependency, help to understand the differences and the similarities between the analysed countries. The domestic governance dimension seems to bridge the frictions between the rather classical inner-state hierarchies and the soft networking tools of cross-border governance in the strict sense. – – In den aktuellen Debatten der 'Border Studies' wird die nationale Ebene eher als nachrangige Kategorie betrachtet. Es gibt jedoch starke Argumente dafür, dass die nationale Ebene eine wichtige Rolle für die Governance von Grenzregionen spielt. Es stellt sich die Frage, welche Formate der Koordination und Vernetzung von Grenzregionen im nationalen Rahmen bestehen. Der Beitrag stellt eine explorative Typologie der nationalen Governance-Settings vor. Die zugrunde liegende empirische Studie zeigt eine große Vielfalt von Governance-Mustern in dreizehn europäischen Ländern. Die synthetische Typologie enthält fünf Ansätze, namentlich die zentralisierte, die dezentrale und die selektive Koordinierung sowie den transnationalen und den Laisser-faire-Ansatz. Vor diesem Hintergrund werden die Erklärungsfaktoren für die Governance-Muster erörtert. Die Staatsstruktur (föderal, zentralistisch) spielt dabei eine wichtige Rolle. Darüber hinaus erklären kontingente politische Strategien, eingebettet in politische Kultur und Pfadabhängigkeit, die Unterschiede und Gemeinsamkeiten zwischen den untersuchten Ländern. Die innerstaatliche Governance-Dimension stellt letztlich eine Überbrückung dar zwischen den eher klassischen innerstaatlichen Hierarchien und den weichen Netzwerkinstrumenten der grenzüberschreitenden Governance im engeren Sinne.
Keywords: 710; Governance; networks; border regions; cooperation; coordination; Netzwerke; Grenzregionen; Kooperation; Koordination